High efficiency of the NH4H2PO4/Mg(OH)2 composite for guaranteeing safety of wood production. (March 2021) - Hangchen, Li; Xiaohui, Shen; Xinxin, Guo; Shunchao, Li; Han, Zhang; Chendong, Zhang; Min, Hua; Xuhai, Pan
Abstract: Currently, China's timber industry is in high demand with the development of real estate. However, there is a certain fire hazard in the production process of wood manufacturing. Once a fire occurs, the fire is violent and the spread is rapid. Therefore, to improve the safety of its production process, ammonium dihydrogen phosphate and magnesium hydroxide were selected to prepare a new composite superfine dry powder, which was denoted as the NH4 H2 PO4 /Mg(OH)2 composite. Furthermore, to figure out dry powders' extinction effect on Class A fire, the wood-crib fire suppression effect of the NH4 H2 PO4 /Mg(OH)2 composite was test, and then compared with that of ultrafine dry powder (UDP) and commercial ABC dry powder (C-ABC) in a 1 m³ chamber. Three parameters of the fire extinguishing process, namely flame extinction time, powder consumption and temperature drop were adopted to measure the fire suppression performance. The results demonstrated that UDP and C-ABC both had a larger flame extinction time and powder consumption than the NH4 H2 PO4 /Mg(OH)2 composite. Besides, a fire (wood cribs) can be extinguished by the NH4 H2 PO4 /Mg(OH)2 composite with the fastest temperature drop and a much-improved toxic gas suppression ability. In short, the NH4 H2 PO4 /Mg(OH)2 composite can better guarantee the safety of the wood processing production process. Moreover, the reasons for performance advantages of the NH4 H2 PO4 /Mg(OH)2 composite were discussed. Highlights: In order to improve the safety of wood production, a new type of composite superfine dry powder was developed using magnesium hydroxide as the additive. The fire suppression effectiveness of C-ABC, UDP and the NH4 H2 PO4 /Mg(OH)2 composite for wood crib fire were compared in a small-sized fire-extinguishing chamber to figure out dry powders' extinction effect on Class A fire. The NH4 H2 PO4 /Mg(OH)2 composite can better guarantee the safety of the wood processing production process with the shortest extinguishing time, least mass of powders consumed, fastest temperature drop and a much-improved toxic gas suppression ability. The reasons for the enhanced suppression effect of the NH4 H2 PO4 /Mg(OH)2 composite were discussed.